A Genetic Algorithm Based Check Pointing and Failure Recovery Scheme in Wireless Sensor Network - Shilpa, Shilpa; Dhadwal, Deepak (International Journal of Computer Sciences and Engineering, 2025)
Mobile nodes are failure prone. An efficient check pointing technique and a failure recovery scheme together can make a Wireless Sensor Network fault-tolerant. For efficient recovery, information of a mobile host should be kept in an organized manner. Efficiency of a recovery scheme can be measured in terms of time and cost. Mobile nodes move randomly causing handoff. Information of a single mobile host gets scattered over a number of mobile support stations that can be at closer or further distance. Recovery time and cost primarily depend on number of mobile support stations from which information to be collected as well as distance among them. Larger the distance, longer the time for communication through message passing. Number of mobile support stations from which information to be recovered and distance among them can be delimited by keeping a Genetic Algorithm threshold value and a distance threshold value respectively in each mobile host. Recovery scheme proposed here applies both the measures. Our work optimizes both failure-free and failure-recovery operation costs